Ultra-Wideband Monostatic Antenna for behind the Wall Detection - Jawad Ali; Roshayati Yahya; Noorsaliza Abdullah; Syarfa Zahirah Sapuan (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This article introduces an ultra-wideband (UWB) shifted arc antenna, designed using Rogers RT-5880 Duroid substrate for the human detection behind the wall. The frequency for this proposed antenna ranges from 2.8 - 15.6 GHz with the gain of around 6.05 dB. A high gain for antenna has been achieved by the implementation of defected ground structure (DGS) method to make it a suitable configuration for through wall detection applications. For the verification of through wall detection configuration, a simulation-based experiment using ground penetrating radar (GPR) technology has been conducted. The results showed that proposed single antenna can act as a monostatic transceiver in order to detect human skin behind the concrete wall. Later, the reflections received from the target have been analyzed to detect and identify the antenna, wall and target for distance calculation.